Model Penyelarasan Kurikulum Berbasis Kemitraan Industri untuk Meningkatkan Relevansi Kompetensi dan Employability Skills Lulusan SMK - Dafit Kurniawan; Bambang Sudarsono; Bakrun Dahlan; Heru Raharjo (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2026)
Vocational High School (SMK) graduates recorded the highest open unemployment rate in Indonesia, reaching 8.62% according to Statistics Indonesia (BPS) data in February 2024. This condition reflects the persistent gap between graduates’ competencies and the needs of the business and industrial sector (DUDI). This study aims to examine the implementation of industry partnership-based curriculum alignment, identify factors affecting its success, and develop a curriculum alignment model that can be adopted by vocational schools with similar contexts, using SMK Muhammadiyah 2 Borobudur as a case study. A qualitative case study approach was employed. Data were collected through in-depth interviews with 12 informants, observations, documentation, and Focus Group Discussions (FGDs). Data were analyzed using the Miles, Huberman, and Saldana interactive model, while data validity was ensured through source and technique triangulation. The findings show that curriculum alignment is implemented through five interconnected stages: industry needs analysis, curriculum synchronization, industry-based learning, employability skills development, and joint evaluation. Collaboration with Hotel Le Temple Borobudur and Plataran Borobudur Resort & Villa significantly improved students’ technical competencies in Hospitality as well as employability skills, particularly communication, teamwork, and professionalism. The study proposes a cyclical curriculum alignment model that enables continuous curriculum improvement in response to changing industry demands and provides a practical framework for strengthening vocational school–industry partnerships to enhance graduate employability.